Black Genius Flexin’: The Radical Potential of a Dreams Assessment in Participatory Research - Dawn X Henderson; Courtney McLaughlin; Denise Page; Joy Spencer; Nadiah Porter; Regina Mays; Rabiatu Barrie (Journal of Participatory Research Methods)
The devastation of COVID-19 and racial violence in 2020 suffocated the dream potential of Black families in North Carolina. That same year, Village of Wisdom (VOW) received rapid funding and leveraged this funding to support an inaugural group of five self-identified Black mothers, aka "mommas," to serve as Parent Researchers. These mommas, trained in participatory research, would embark upon a project to understand the needs of Black students, their parents, and teachers during COVID-19 and challenges associated with remote learning. The Dreams Assessment then emerged as a communal assessment to activate the dream potentials of the mommas, VOW, and spark a movement of amplifying Black parent wisdom as co-authors of research, co-designers, and creators. This paper uses storytelling to reflect on conducting the Dreams Assessment from the perspective of those Black mommas and the "other" mothers and centers communal weaving through shared discoveries and lessons learned. The authors offer the Dreams Assessment as a radical and reimagined participatory research approach from a community-driven and liberatory lens.